The significance of intra-abdominal pressure on postural stabilization: A low back pain case report - Novak, J.; Jacisko, J.; Stverakova, T.; Juehring, D.; Sembera, M.; Kolar, P.; Kobesova, A. (Slovak Journal of Sport Science, 2021)
Intra-abdominal pressure is a hydraulic pressure within the abdominal cavity. Previous studies confirmed its direct association with both spinal stability and spinal unloading. The literature review part of the paper summarizes intra-abdominal pressure physiology and pathophysiology and explains the underlying mechanisms of Intra-abdominal pressure regulation and its effects on the human body, especially spinal stability. Current methods of invasive and non-invasive intra-abdominal pressure measurement are described in detail. Second part of a paper presents a case report of a competitive athlete suffering from low back pain. The functional assessment and treatment focused on quality of patient`s trunk stabilization. Training following principles of Dynamic Neuromuscular Stabilization resulted in better ability to activate abdominal wall muscles which is a critical mechanism of Intra-abdominal pressure regulation and in this case caused significant low back pain reduction. The effect of the therapy was evaluated by DNS Brace which measures activity of the abdominal wall, thus Intra-abdominal pressure indirectly, along with clinical Dynamic Neuromuscular Stabilization assessment tests.